2009
DOI: 10.1504/ijmtm.2009.023931
|View full text |Cite
|
Sign up to set email alerts
|

Rapid design of tool-wear condition monitoring systems for turning processes using novelty detection

Abstract: Condition monitoring systems of manufacturing processes have been recognised in recent years as one of the key technologies that provide the competitive advantage in many manufacturing environments. It is capable of providing essential means to reduce cost, increase productivity, improve quality and prevent damage to the machine or work-piece. Turning operations are considered one of the most common manufacturing processes in industry. It is used to manufacture different round objects such as shafts, spindles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…However, automated signal processing and analysis is needed to extract the important information from the signals (i.e. Sensory Characteristic Features (SCFs)) [1,6,7]. The test from the first tool is used to investigate the process characteristic and to select the sensitive Sensory Characteristic Features…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, automated signal processing and analysis is needed to extract the important information from the signals (i.e. Sensory Characteristic Features (SCFs)) [1,6,7]. The test from the first tool is used to investigate the process characteristic and to select the sensitive Sensory Characteristic Features…”
Section: Resultsmentioning
confidence: 99%
“…The most critical aspect of the design of a condition monitoring system is how to select a suitable sensor or signal processing system to design the experiments. The authors in previous publications have suggested an Automated Signal and Signal Processing Selection System (ASPS) [6,7]. This is preformed by processing the available sensory signals with a selection of signal processing algorithms.…”
Section: The Design Of the Condition Monitoring Systemmentioning
confidence: 99%
See 3 more Smart Citations